Morality and Trust in Impersonal Relationships - Gerhard Minnameier; Tim Jonas Bonowski (ZBW - Leibniz Information Centre for Economics, 2021)
Experiments with the trust game reveal that people are generally more trusting and trustworthy than can be explained by profit maximizing strategies. Usual attempts to explain this social preferences. Contrary to such a view, we suggest that trust and trustworthiness depend on a specific kind of morality that functions as a social norm and therefore comes with specific moral punishments and rewards. Since these moral incentives are confounded with material incentives in the trust game, an augmented version of the game is used, in which moral communication without material consequences is possible. In comparison with the original trust game, we find higher levels of both trust and trustworthiness in the augmented game. We also find that these levels remain stable across ten rounds of randomized anonymous interaction.
Keywords: D90; 330